"Don't drop the patient:" Health information in a postpandemic world. Issue 2 (15th June 2022) - Hesse, Bradford W.; Aronoff‐Spencer, Eliah; Ahern, David K.; Mullett, Timothy W.; Gibbons, Chris; Chih, Ming‐Yuan; Hubenko, Alexandra; Koop, Barbara
Abstract: Building on technological advances and existing currents of a healthcare system in flux, the COVID‐19 pandemic has brought about perhaps the most rapid transformation in human health and healthcare seen in our times. Even as new opportunities such as telemedicine, remote care, and rapid precision health practices are poised to improve access and care for populations, the increasing sophistication of this transformation has brought with it new levels of complexity, fragmentation, and silos. The singular outcome of this system is the vast number of novel ways for miscommunication, loss of information in transition, and breakdowns in the cognitive continuity of care. We refer to these failure modes as "dropping the patient" and adopt a mantra of "don't drop the patient" which examines our emerging health system in the context of patient‐centered continuity. In this light, we investigate bright spots and pitfalls, and we offer insights from Human Factors Engineering, Human Centered Design, and Human System Integration, which provide tools and methods to codesign and codevelop continuous and resilient services that are inclusive, sustainable, and effective. Key points: Technological advances, along with global pressures on health care from events such as the COVID‐19 pandemic, have created an information environment in healthcare that is in flux. On the positive side, a widespread adoption of electronic health information systems can transcend barriers to access by moving care to patients through telemedical consults, remote patient monitoring, online self‐management, appointment management, treatment tracking, and population health monitoring. On the negative side, overlaying complex information technologies on healthcare networks that may already be fragmented may increase risks for communication errors. Strengthening communication systems in health care will require an application of human‐centered design principles not just at the level of individual technologies but at the systems level in which technologies, medical protocols, professional training, and patient experiences interact. A key focus of design efforts at the human‐system level is to create a fault‐tolerant sociotechnical environment that minimizes discontinuity in care; that is, to create a new biomedical ethos of "not dropping the patient" as the standard in global health care.